Torn ankle ligaments in elite handball: Does a player require surgery? - d`Hooghe, P.; Giza, E.; Longo, U. (ASPETAR Sports Medicine Journal, 2014)
The major cause of ligamentous ankle lesions in elite handball players involves plantarflexed and inversion ankle movements. Due to the decreased stability in that postural position, and due to sport-specific cutting actions, severe inversion/eversion injuries can occur. Acute lateral ankle injury must be initially managed with functional treatment. A short immobilisation period should be followed by proprioception training to obtain full recovery of ankle function. When chronic lateral ankle instability occurs (following repeated episodes of ankle sprains) and/or when functional rehabilitation fails, surgery is required. Bröstrom-Gould anatomic repair can be considered the most successful surgical procedure, especially for an explosive impact sport such as elite handball.